2017
DOI: 10.1007/s40801-017-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hip Fracture in Older People Using Selective Serotonin Reuptake Inhibitors and Other Psychoactive Medicines Concurrently: A Matched Case–Control Study in Australia

Abstract: BackgroundFew studies have assessed the risk of hip fracture following concurrent use of psychoactive medicines, and none has investigated combinations with selective serotonin reuptake inhibitors.ObjectivesTo assess the risk of hip fracture in older people as a result of concurrent use of selective serotonin reuptake inhibitors and other psychoactive medicines.MethodsA matched case–control design was employed. Cases were Australian Government Department of Veterans’ Affairs beneficiaries aged over 65 years wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Particularly, the results showed that zopiclone was frequently co‐prescribed with other drugs prior to a fracture event. Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Particularly, the results showed that zopiclone was frequently co‐prescribed with other drugs prior to a fracture event. Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible …”
Section: Discussionsupporting
confidence: 75%
“…Several studies have shown that z hypnotics significantly increase the risk of fracture in older adults, and our results are biologically plausible. [30][31][32][33][34] The sensitivity analyses repeated with weekly (7-day) and monthly (30-day) time windows did not change the overall results. These time windows were chosen to align with the best practice recommendations for conducting a case-crossover study.…”
Section: Discussionmentioning
confidence: 86%
“…Among numerous drugs used for HPI-related diseases many are well known to contribute to OP/OFs. In regard to OP, these include corticosteroids, antidepressants (especially, selective serotonin- and serotonin-norepinephrine reuptake inhibitors), glitazones, opioids, benzodiazepines, antipsychotics, antiparkinsonian drugs, antiepileptics, PPIs, H2RA, thyroxine, furosemide, aromatase inhibitors, gonadotropin releasing hormone (GnRH) agonists, whereas hormone replacement therapy with estrogen, thiazides, angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs), spironolactone, beta-blockers, statins, antihistamines, metformin, sulphonylureas, glucagon-like peptide-1 receptor agonists (liraglutide) and nitrates have shown an osteoprotective effect [ 316 , 521 , 522 , 523 , 524 , 525 , 526 , 527 , 528 , 529 , 530 , 531 , 532 , 533 , 534 , 535 , 536 , 537 , 538 , 539 , 540 , 541 , 542 , 543 , 544 , 545 , 546 , 547 , 548 , 549 , 550 , 551 , 552 , 553 , 554 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…An Australian matched case-control study using data from the Australian Government Department of Veterans’ Affairs (DVA) assessed the risk of hip fracture following starting and ongoing use of SSRIs, either alone, or in combination with other psychotropic drugs 12. The study included 8828 veterans with hip fracture and 35,310 matched controls of the same age and gender, and examined their medicine use in the previous six months.…”
Section: Psychotropic Drugs and Hip Fracturementioning
confidence: 99%
“…The study included 8828 veterans with hip fracture and 35,310 matched controls of the same age and gender, and examined their medicine use in the previous six months. The average age of the cohort was 88 years and 63% were women 12…”
Section: Psychotropic Drugs and Hip Fracturementioning
confidence: 99%